High-performance compound bentonite for drilling mud and preparation method of high-performance compound bentonite

By compounding and sodium-treated bentonite A, B and C with high montmorillonite content, the problems of insufficient viscosity and excessive filtration loss in complex drilling scenarios were solved, achieving the stability and salt resistance of high-performance drilling mud and reducing processing costs.

CN120865857APending Publication Date: 2025-10-31WUHU FEISHANG NONMETAL MATERIAL
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510900725.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In existing technologies, single raw ore is difficult to meet the performance requirements of complex drilling scenarios such as deep wells, salt gypsum layers, and highly mineralized formations, resulting in problems such as weak cuttings suspension capacity, high risk of wellbore collapse, insufficient viscosity, or excessive filtration loss.

Method used

A high-performance compound bentonite is formed by combining bentonite A with high montmorillonite content, bentonite B with high expansion ratio, and bentonite C with medium water absorption rate, and by sodium carbonate, sodium humate and surfactant treatment. The viscosity and salt resistance are improved through sodium treatment and aging.

Benefits of technology

It enables the improvement of drilling fluid viscosity and filtration loss, stabilization of wellbore, reduction of dependence on high-grade ore, and improvement of comprehensive utilization of mineral resources on the basis of medium and low grade raw ore, while with lower processing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses high-performance compound bentonite for drilling mud and a preparation method of the high-performance compound bentonite, and relates to the technical field of bentonite, and the high-performance compound bentonite comprises the following raw materials in parts by weight: 80-100 parts of mixed bentonite, 4-6 parts of sodium carbonate, 0.3-0.5 part of sodium humate, 0.2-0.4 part of triethanolamine and 0.2-0.4 part of a surfactant. Through the synergistic effect of the bentonite A with the high montmorillonite content, the bentonite B with the high expansion multiple and the bentonite C with the medium water absorption rate, in cooperation with sodium modification and assistant regulation and control, the product viscosity is stable, the requirement for the sand-carrying capacity of the drilling fluid is met, the filter loss is far lower than that of a traditional product, the filter cake thickness is smaller than or equal to 1.2 mm, the structure is compact, water permeation can be effectively controlled, the well wall can be stabilized, and the drilling fluid can be used for well drilling. The problem that single raw ore is insufficient in viscosity or too high in filter loss is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of bentonite technology, specifically to a high-performance compound bentonite for drilling mud and its preparation method. Background Technology

[0002] Bentonite is a core functional material in drilling mud. Through the hydration and expansion of montmorillonite, it forms a colloidal system that plays crucial roles in suspending rock cuttings, stabilizing the wellbore, cooling the drill bit, and transmitting hydrodynamic forces, directly impacting the efficiency and safety of oil and natural gas extraction. In drilling engineering, the viscosity and filtration loss of the mud system are key performance indicators, and these two indicators primarily depend on the montmorillonite content, expansion performance, and hydration capacity of the bentonite.

[0003] However, with the deepening of mineral resource development, the reserves of high-grade bentonite ore have sharply decreased, and most of the ore circulating in the market is of medium and low grade. Single ore can no longer meet the performance requirements of complex drilling scenarios, such as deep wells, salt gypsum layers, and high-mineralization formations. ① Low montmorillonite content raw ore has insufficient viscosity after hydration, resulting in weak rock cuttings suspension capacity, which easily leads to wellbore blockage; ② The filter cake formed by raw ore with low expansion ratio has a loose structure and high filtration loss, which can easily lead to well wall collapse. Summary of the Invention

[0004] The purpose of this invention is to provide a high-performance compound bentonite for drilling mud and its preparation method, in order to solve the problem mentioned in the background art that single raw ore is difficult to meet the performance requirements of complex drilling scenarios, such as deep wells, salt gypsum layers, and high mineralization formations.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a high-performance compound bentonite for drilling mud, comprising the following raw materials in parts by weight: 80-100 parts of mixed bentonite, 4-6 parts of sodium carbonate, 0.3-0.5 parts of sodium humate, 0.2-0.4 parts of triethanolamine and 0.2-0.4 parts of surfactant; The mixed bentonite is made by mixing bentonite A, bentonite B and bentonite C, and the ratio of bentonite A, bentonite B and bentonite C is 1:1:1 to 2:2:1.

[0006] Preferably, the bentonite A contains 56.3% montmorillonite, has an expansion ratio of 16 ml / 2g, and a water absorption rate of 221%; the bentonite B contains 48.9% montmorillonite, has an expansion ratio of 23 ml / 2g, and a water absorption rate of 189%; and the bentonite C contains 52.8% montmorillonite, has an expansion ratio of 15 ml / 2g, and a water absorption rate of 208%.

[0007] Preferably, the surfactant is selected from sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether.

[0008] A method for preparing high-performance compound bentonite for drilling mud includes the following steps: I. Bentonite A, Bentonite B and Bentonite C are dried separately, then ground and pulverized, and finally sieved through a 150-mesh standard sieve. II. Weigh out the treated bentonite A, bentonite B and bentonite C according to the proportions. Add bentonite A, bentonite B and bentonite C into the mixer and mix to obtain mixed bentonite. Set the mixing speed to 15 r / min and the mixing time to 30 minutes. III. Weigh out a quantity of the mixed bentonite and place it in the mixing tank of a high-speed mixer, while simultaneously preparing a sodium carbonate solution; IV. Add deionized water to the mixing tank, and control the water temperature at 25±2℃. Turn on the mixer and stir at a low speed of 3000r / min for 5 minutes to initially disperse the mixed bentonite. Slowly pour in the prepared sodium carbonate solution to carry out the sodiumization reaction. Adjust the speed to 11000r / min and stir for 20 to 25 minutes. During this period, use an infrared thermometer to monitor the temperature of the liquid. If it exceeds 35℃, stop stirring for 2 minutes to cool down. V. Weigh out sodium humate, triethanolamine and surfactant separately. After stirring for 15 minutes, keep the speed at 11000 r / min and add sodium humate, triethanolamine and surfactant to the mixing tank in sequence. Continue stirring for 5 minutes to ensure that the mud bentonite additive and the mixed bentonite particles are fully adsorbed. VI. After mixing, turn off the mixer and transfer the liquid to a constant temperature maturation tank. Let it stand at a constant temperature of 25°C for 24 hours for maturation treatment, and finally produce high-performance compound bentonite. VII. After the samples pass the test, they should be sealed and stored.

[0009] Preferably, in step I, the drying process includes the following steps: A1. Take bentonite A, bentonite B and bentonite C, put them into the dryer respectively, set the drying temperature to 60-80℃, dry for 4-6 hours, and take them out when the moisture content is ≤5%. A2. The dried bentonite is then fed into a vibratory mill and an air jet mill in sequence. The vibratory mill rotates at 1200 r / min and is pulverized to a particle size ≤1 mm. The air jet mill operates at a pressure of 0.6-0.8 MPa and is pulverized to a particle size ≤106 μm. A3. After crushing, the material is screened through a 150-mesh vibrating screen. The residual particles on the screen are returned to the airflow pulverizer for re-crushing, and the material under the screen is temporarily stored in a sealed storage tank.

[0010] Preferably, in step II, during the preparation of the mixed bentonite, the material adhesion to the wall is checked every 10 minutes through the observation window. If the amount of material adhering to the wall is ≥5%, the machine is stopped and the tank wall is purged with 0.4MPa compressed air to ensure that the material is fully involved in the mixing.

[0011] Preferably, in step III, the preparation of the sodium carbonate solution includes the following steps: B1. Calculate the amount of sodium carbonate to be used based on 4% to 6% of the mass of the mixed bentonite and weigh it into the mixer. B2. Add deionized water to the stirrer and stir thoroughly to completely dissolve the sodium carbonate. B3. During the dissolution of sodium carbonate, measure the solution temperature. If it exceeds 25°C, place the beaker at room temperature for 5-10 minutes and cool it to 20-25°C. B4. After preparation, collect the sodium carbonate solution for later use.

[0012] Preferably, in step VI, during the maturation process, the bottom agitator is turned on for 5 minutes every 6 hours, and the agitation speed is 50 r / min.

[0013] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, through the synergistic effect of bentonite A with high montmorillonite content, bentonite B with high expansion ratio, and bentonite C with medium water absorption rate, combined with sodium treatment and additive regulation, the product viscosity is stable and meets the requirements of drilling fluid sand carrying capacity. The filtration loss is much lower than that of traditional products. The filter cake thickness is ≤1.2mm and the structure is dense, which can effectively control water penetration and stabilize the well wall, solving the problem of insufficient viscosity or excessive filtration loss of single raw ore. 2. In this invention, through sodium treatment and the synergistic effect of sodium humate and triethanolamine, the salt resistance and high temperature stability of this invention are outstanding. The high degree of sodium treatment makes the montmorillonite crystal layer more firmly bonded and less prone to depolymerization at high temperatures. The synergistic effect of sodium humate and triethanolamine can still maintain the hydration film on the particle surface at high temperatures. 3. In view of the current situation of depletion of high-grade bentonite ore, this invention transforms medium and low-grade ore into high-performance products through compounding technology. It does not rely on natural high-sodium bentonite, improves the comprehensive utilization rate of mineral resources, reduces dependence on high-quality ore, and the proportion of sodium carbonate and additives is low, resulting in lower processing costs. When produced on a large scale, the unit energy consumption can be controlled at a low level. Detailed Implementation

[0014] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] The present invention will be further described below with reference to embodiments.

[0016] Example 1: This example provides a high-performance compound bentonite for drilling mud, comprising the following raw materials in parts by weight: 80 parts of mixed bentonite, 4 parts of sodium carbonate, 0.3 parts of sodium humate, 0.2 parts of triethanolamine and 0.2 parts of surfactant; The mixed bentonite is made by mixing bentonite A, bentonite B, and bentonite C in a ratio of 1:1:1. Bentonite A contains 56.3% montmorillonite, has an expansion ratio of 16 ml / 2g, and a water absorption rate of 221%. Bentonite B contains 48.9% montmorillonite, has an expansion ratio of 23 ml / 2g, and a water absorption rate of 189%. Bentonite C contains 52.8% montmorillonite, has an expansion ratio of 15 ml / 2g, and a water absorption rate of 208%. Sodium dodecyl sulfate was selected as the surfactant. A method for preparing high-performance compound bentonite for drilling mud includes the following steps: I. Bentonite A, Bentonite B and Bentonite C are dried separately, then ground and pulverized, and finally sieved through a 150-mesh standard sieve. The drying process is as follows: Bentonite A, Bentonite B, and Bentonite C are taken and fed into a dryer respectively. The drying temperature is set to 60-80℃, and the drying time is 4-6 hours. When the moisture content is ≤5%, the bentonite is taken out. The dried bentonite is then fed into a vibrating mill and an air jet mill in sequence. The vibrating mill rotates at 1200 r / min and is pulverized to a particle size ≤1 mm. The air jet mill operates at a pressure of 0.6-0.8 MPa and is pulverized to a particle size ≤106 μm. The pulverized material is then screened through a 150-mesh vibrating screen. The residual particles on the screen are returned to the air jet mill for re-pulverization, and the material under the screen is temporarily stored in a sealed storage tank. II. Weigh out the treated bentonite A, bentonite B and bentonite C according to the proportions. Add bentonite A, bentonite B and bentonite C into the mixer and mix to obtain mixed bentonite. Set the mixing speed to 15 r / min and the mixing time to 30 minutes. During the preparation of mixed bentonite, the material adheres to the wall every 10 minutes through the observation window. If the amount of material adhering to the wall is ≥5%, the machine is stopped and the tank wall is purged with 0.4MPa compressed air to ensure that the material is fully involved in the mixing. III. Weigh out a quantity of the mixed bentonite and place it in the mixing tank of a high-speed mixer, while simultaneously preparing a sodium carbonate solution; The process for preparing the sodium carbonate solution is as follows: First, calculate the amount of sodium carbonate needed based on 4% to 6% of the mass of the mixed bentonite and weigh it into a stirrer; then add deionized water to the stirrer and stir thoroughly to completely dissolve the sodium carbonate; during the dissolution process, measure the solution temperature. If it exceeds 25°C, place the beaker at room temperature for 5 to 10 minutes to cool it to 20 to 25°C; after preparation, collect the sodium carbonate solution for later use. IV. Add deionized water to the mixing tank, and control the water temperature at 25±2℃. Turn on the mixer and stir at a low speed of 3000r / min for 5 minutes to initially disperse the mixed bentonite. Slowly pour in the prepared sodium carbonate solution to carry out the sodiumization reaction. Adjust the speed to 11000r / min and stir for 20 to 25 minutes. During this period, use an infrared thermometer to monitor the temperature of the liquid. If it exceeds 35℃, stop stirring for 2 minutes to cool down. V. Weigh out sodium humate, triethanolamine and surfactant separately. After stirring for 15 minutes, keep the speed at 11000 r / min and add sodium humate, triethanolamine and surfactant to the mixing tank in sequence. Continue stirring for 5 minutes to ensure that the mud bentonite additive and the mixed bentonite particles are fully adsorbed. VI. After mixing, turn off the mixer and transfer the liquid to a constant temperature maturation tank. Let it stand at a constant temperature of 25°C for 24 hours for maturation treatment, and finally produce high-performance compound bentonite. During the maturation process, the bottom agitator is turned on for 5 minutes every 6 hours, and the stirring speed is 50 r / min. VII. After the samples pass the test, they should be sealed and stored.

[0017] Example 2: This example provides a high-performance compound bentonite for drilling mud, comprising the following raw materials in parts by weight: 90 parts of mixed bentonite, 5 parts of sodium carbonate, 0.4 parts of sodium humate, 0.3 parts of triethanolamine and 0.3 parts of surfactant; The mixed bentonite is made by mixing bentonite A, bentonite B, and bentonite C in a ratio of 1.5:1.5:1. Bentonite A contains 56.3% montmorillonite, has an expansion ratio of 16 ml / 2g, and a water absorption rate of 221%; bentonite B contains 48.9% montmorillonite, has an expansion ratio of 23 ml / 2g, and a water absorption rate of 189%; and bentonite C contains 52.8% montmorillonite, has an expansion ratio of 15 ml / 2g, and a water absorption rate of 208%. Sodium dodecyl sulfate was selected as the surfactant. A method for preparing high-performance compound bentonite for drilling mud includes the following steps: I. Bentonite A, Bentonite B and Bentonite C are dried separately, then ground and pulverized, and finally sieved through a 150-mesh standard sieve. The drying process is as follows: Bentonite A, Bentonite B, and Bentonite C are taken and fed into a dryer respectively. The drying temperature is set to 60-80℃, and the drying time is 4-6 hours. When the moisture content is ≤5%, the bentonite is taken out. The dried bentonite is then fed into a vibrating mill and an air jet mill in sequence. The vibrating mill rotates at 1200 r / min and is pulverized to a particle size ≤1 mm. The air jet mill operates at a pressure of 0.6-0.8 MPa and is pulverized to a particle size ≤106 μm. The pulverized material is then screened through a 150-mesh vibrating screen. The residual particles on the screen are returned to the air jet mill for re-pulverization, and the material under the screen is temporarily stored in a sealed storage tank. II. Weigh out the treated bentonite A, bentonite B and bentonite C according to the proportions. Add bentonite A, bentonite B and bentonite C into the mixer and mix to obtain mixed bentonite. Set the mixing speed to 15 r / min and the mixing time to 30 minutes. During the preparation of mixed bentonite, the material adheres to the wall every 10 minutes through the observation window. If the amount of material adhering to the wall is ≥5%, the machine is stopped and the tank wall is purged with 0.4MPa compressed air to ensure that the material is fully involved in the mixing. III. Weigh out a quantity of the mixed bentonite and place it in the mixing tank of a high-speed mixer, while simultaneously preparing a sodium carbonate solution; The process for preparing the sodium carbonate solution is as follows: First, calculate the amount of sodium carbonate needed based on 4% to 6% of the mass of the mixed bentonite and weigh it into a stirrer; then add deionized water to the stirrer and stir thoroughly to completely dissolve the sodium carbonate; during the dissolution process, measure the solution temperature. If it exceeds 25°C, place the beaker at room temperature for 5 to 10 minutes to cool it to 20 to 25°C; after preparation, collect the sodium carbonate solution for later use. IV. Add deionized water to the mixing tank, and control the water temperature at 25±2℃. Turn on the mixer and stir at a low speed of 3000r / min for 5 minutes to initially disperse the mixed bentonite. Slowly pour in the prepared sodium carbonate solution to carry out the sodiumization reaction. Adjust the speed to 11000r / min and stir for 20 to 25 minutes. During this period, use an infrared thermometer to monitor the temperature of the liquid. If it exceeds 35℃, stop stirring for 2 minutes to cool down. V. Weigh out sodium humate, triethanolamine and surfactant separately. After stirring for 15 minutes, keep the speed at 11000 r / min and add sodium humate, triethanolamine and surfactant to the mixing tank in sequence. Continue stirring for 5 minutes to ensure that the mud bentonite additive and the mixed bentonite particles are fully adsorbed. VI. After mixing, turn off the mixer and transfer the liquid to a constant temperature maturation tank. Let it stand at a constant temperature of 25°C for 24 hours for maturation treatment, and finally produce high-performance compound bentonite. During the maturation process, the bottom agitator is turned on for 5 minutes every 6 hours, and the stirring speed is 50 r / min. VII. After the samples pass the test, they should be sealed and stored.

[0018] Example 3: This example provides a high-performance compound bentonite for drilling mud, comprising the following raw materials in parts by weight: 100 parts of mixed bentonite, 6 parts of sodium carbonate, 0.5 parts of sodium humate, 0.4 parts of triethanolamine and 0.4 parts of surfactant; The mixed bentonite is made by mixing bentonite A, bentonite B, and bentonite C in a ratio of 2:2:1. Bentonite A contains 56.3% montmorillonite, has an expansion ratio of 16 ml / 2g, and a water absorption rate of 221%. Bentonite B contains 48.9% montmorillonite, has an expansion ratio of 23 ml / 2g, and a water absorption rate of 189%. Bentonite C contains 52.8% montmorillonite, has an expansion ratio of 15 ml / 2g, and a water absorption rate of 208%. Sodium dodecyl sulfate was selected as the surfactant. A method for preparing high-performance compound bentonite for drilling mud includes the following steps: I. Bentonite A, Bentonite B and Bentonite C are dried separately, then ground and pulverized, and finally sieved through a 150-mesh standard sieve. The drying process is as follows: Bentonite A, Bentonite B, and Bentonite C are taken and fed into a dryer respectively. The drying temperature is set to 60-80℃, and the drying time is 4-6 hours. When the moisture content is ≤5%, the bentonite is taken out. The dried bentonite is then fed into a vibrating mill and an air jet mill in sequence. The vibrating mill rotates at 1200 r / min and is pulverized to a particle size ≤1 mm. The air jet mill operates at a pressure of 0.6-0.8 MPa and is pulverized to a particle size ≤106 μm. The pulverized material is then screened through a 150-mesh vibrating screen. The residual particles on the screen are returned to the air jet mill for re-pulverization, and the material under the screen is temporarily stored in a sealed storage tank. II. Weigh out the treated bentonite A, bentonite B and bentonite C according to the proportions. Add bentonite A, bentonite B and bentonite C into the mixer and mix to obtain mixed bentonite. Set the mixing speed to 15 r / min and the mixing time to 30 minutes. During the preparation of mixed bentonite, the material adheres to the wall every 10 minutes through the observation window. If the amount of material adhering to the wall is ≥5%, the machine is stopped and the tank wall is purged with 0.4MPa compressed air to ensure that the material is fully involved in the mixing. III. Weigh out a quantity of the mixed bentonite and place it in the mixing tank of a high-speed mixer, while simultaneously preparing a sodium carbonate solution; The process for preparing the sodium carbonate solution is as follows: First, calculate the amount of sodium carbonate needed based on 4% to 6% of the mass of the mixed bentonite and weigh it into a stirrer; then add deionized water to the stirrer and stir thoroughly to completely dissolve the sodium carbonate; during the dissolution process, measure the solution temperature. If it exceeds 25°C, place the beaker at room temperature for 5 to 10 minutes to cool it to 20 to 25°C; after preparation, collect the sodium carbonate solution for later use. IV. Add deionized water to the mixing tank, and control the water temperature at 25±2℃. Turn on the mixer and stir at a low speed of 3000r / min for 5 minutes to initially disperse the mixed bentonite. Slowly pour in the prepared sodium carbonate solution to carry out the sodiumization reaction. Adjust the speed to 11000r / min and stir for 20 to 25 minutes. During this period, use an infrared thermometer to monitor the temperature of the liquid. If it exceeds 35℃, stop stirring for 2 minutes to cool down. V. Weigh out sodium humate, triethanolamine and surfactant separately. After stirring for 15 minutes, keep the speed at 11000 r / min and add sodium humate, triethanolamine and surfactant to the mixing tank in sequence. Continue stirring for 5 minutes to ensure that the mud bentonite additive and the mixed bentonite particles are fully adsorbed. VI. After mixing, turn off the mixer and transfer the liquid to a constant temperature maturation tank. Let it stand at a constant temperature of 25°C for 24 hours for maturation treatment, and finally produce high-performance compound bentonite. During the maturation process, the bottom agitator is turned on for 5 minutes every 6 hours, and the stirring speed is 50 r / min. VII. After the samples pass the test, they should be sealed and stored.

[0019] Example 4: This example provides a high-performance compound bentonite for drilling mud, comprising the following raw materials in parts by weight: 850 parts of mixed bentonite, 5 parts of sodium carbonate, 0.3 parts of sodium humate, 0.4 parts of triethanolamine and 0.3 parts of surfactant; The mixed bentonite is made by mixing bentonite A, bentonite B, and bentonite C in a ratio of 1.5:1.5:1. Bentonite A contains 56.3% montmorillonite, has an expansion ratio of 16 ml / 2g, and a water absorption rate of 221%; bentonite B contains 48.9% montmorillonite, has an expansion ratio of 23 ml / 2g, and a water absorption rate of 189%; and bentonite C contains 52.8% montmorillonite, has an expansion ratio of 15 ml / 2g, and a water absorption rate of 208%. Sodium dodecyl sulfate was selected as the surfactant. A method for preparing high-performance compound bentonite for drilling mud includes the following steps: I. Bentonite A, Bentonite B and Bentonite C are dried separately, then ground and pulverized, and finally sieved through a 150-mesh standard sieve. The drying process is as follows: Bentonite A, Bentonite B, and Bentonite C are taken and fed into a dryer respectively. The drying temperature is set to 60-80℃, and the drying time is 4-6 hours. When the moisture content is ≤5%, the bentonite is taken out. The dried bentonite is then fed into a vibrating mill and an air jet mill in sequence. The vibrating mill rotates at 1200 r / min and is pulverized to a particle size ≤1 mm. The air jet mill operates at a pressure of 0.6-0.8 MPa and is pulverized to a particle size ≤106 μm. The pulverized material is then screened through a 150-mesh vibrating screen. The residual particles on the screen are returned to the air jet mill for re-pulverization, and the material under the screen is temporarily stored in a sealed storage tank. II. Weigh out the treated bentonite A, bentonite B and bentonite C according to the proportions. Add bentonite A, bentonite B and bentonite C into the mixer and mix to obtain mixed bentonite. Set the mixing speed to 15 r / min and the mixing time to 30 minutes. During the preparation of mixed bentonite, the material adheres to the wall every 10 minutes through the observation window. If the amount of material adhering to the wall is ≥5%, the machine is stopped and the tank wall is purged with 0.4MPa compressed air to ensure that the material is fully involved in the mixing. III. Weigh out a quantity of the mixed bentonite and place it in the mixing tank of a high-speed mixer, while simultaneously preparing a sodium carbonate solution; The process for preparing the sodium carbonate solution is as follows: First, calculate the amount of sodium carbonate needed based on 4% to 6% of the mass of the mixed bentonite and weigh it into a stirrer; then add deionized water to the stirrer and stir thoroughly to completely dissolve the sodium carbonate; during the dissolution process, measure the solution temperature. If it exceeds 25°C, place the beaker at room temperature for 5 to 10 minutes to cool it to 20 to 25°C; after preparation, collect the sodium carbonate solution for later use. IV. Add deionized water to the mixing tank, and control the water temperature at 25±2℃. Turn on the mixer and stir at a low speed of 3000r / min for 5 minutes to initially disperse the mixed bentonite. Slowly pour in the prepared sodium carbonate solution to carry out the sodiumization reaction. Adjust the speed to 11000r / min and stir for 20 to 25 minutes. During this period, use an infrared thermometer to monitor the temperature of the liquid. If it exceeds 35℃, stop stirring for 2 minutes to cool down. V. Weigh out sodium humate, triethanolamine and surfactant separately. After stirring for 15 minutes, keep the speed at 11000 r / min and add sodium humate, triethanolamine and surfactant to the mixing tank in sequence. Continue stirring for 5 minutes to ensure that the mud bentonite additive and the mixed bentonite particles are fully adsorbed. VI. After mixing, turn off the mixer and transfer the liquid to a constant temperature maturation tank. Let it stand at a constant temperature of 30℃ for 24 hours for maturation treatment, and finally produce high-performance compound bentonite. During the maturation process, the bottom agitator is turned on for 5 minutes every 6 hours, and the stirring speed is 50 r / min. VII. After the samples pass the test, they should be sealed and stored.

[0020] Comparative Example 1: The high-performance compound bentonite for drilling mud and its preparation method provided in this example are roughly the same as those in Example 1, except that sodium carbonate is not used and there is no sodium treatment.

[0021] Comparative Example 2: The high-performance compound bentonite for drilling mud and its preparation method provided in this example are roughly the same as those in Example 1, except that bentonite C is not added.

[0022] Comparative Example 3: The high-performance compound bentonite for drilling mud and its preparation method provided in this example are roughly the same as those in Example 1, except that the maturation time is 12 hours. Performance testing and results analysis

[0023] The drilling muds prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests using high-performance compound bentonite, according to the testing standard GB / T20973-2020, and the relevant data were recorded in Table 1. (1) Basic performance: Viscosity: Using a six-speed rotational viscometer, readings were taken at 600 r / min and 300 r / min to calculate apparent viscosity (AV), plastic viscosity (PV), and dynamic shear force (YP).

[0024] Calculation formula: AV = 600 r / min reading / 2 (mPa·s), YP = 300 r / min reading - PV (Pa).

[0025] Filtration loss: API filtration loss meter, filtration loss (mL) over 30 minutes at room temperature and pressure, while simultaneously recording the filter cake thickness (mm).

[0026] (2) Salt resistance: Add 5% NaCl to the mud, stir at high speed for 20 minutes, and then repeat the tests on viscosity and filtration loss to calculate the performance retention rate (e.g., viscosity retention rate = viscosity after salt addition / original viscosity × 100%).

[0027] (3) High temperature stability: The mud was placed in a high-temperature roller furnace and aged at 150°C for 16 hours. After cooling to room temperature, the viscosity and filtration loss were tested.

[0028] (4) Particle size distribution: Laser particle size analyzer is used to determine particle size distribution, with a focus on the proportion of particles <5μm.

[0029] Sample preparation: Three parallel samples (500g each) were taken for each example / comparative example to ensure that the test result error was ≤5%.

[0030] Before testing, the sample was equilibrated in a constant temperature environment of 25℃ for 2 hours to eliminate the influence of temperature on viscosity.

[0031] Test order: Basic performance → Salt resistance → High temperature stability (to avoid interference from previous tests on subsequent results).

[0032] Each test was repeated 3 times, and the average value was recorded. Table 1: Experimental Data Recording Table

[0033]

[0034] As shown in Table 1, compared with the comparative example, the high-performance compound bentonite prepared in Examples 1-4 can achieve high performance on the basis of medium and low grade raw ore by optimizing the mixing ratio and sodiumization intensity, providing technical support for complex drilling scenarios. Viscosity increased with increasing bentonite A / bentonite B ratio and sodium carbonate dosage. This is because: the increased proportion of bentonite A (high montmorillonite) (1:1:1 → 2:2:1) provides more hydration framework, enhancing the cohesion of the colloidal system; increasing sodium carbonate dosage from 4% to 6% promotes the replacement of more calcium / magnesium ions with sodium ions, enhancing the hydration and swelling capacity of montmorillonite, strengthening interparticle entanglement, and increasing viscosity. Comparative Example 1 had a viscosity of only 30 mPa·s because calcium-based montmorillonite is difficult to hydrate and cannot form a continuous colloidal network, proving that sodiumization is a core prerequisite for increasing viscosity. Comparative Example 2 had a viscosity of 43 mPa·s, lower than Example 2, because the lack of bentonite C led to a decrease in the system's water retention capacity and insufficient particle dispersion, indirectly reducing viscosity. Comparative Example 3 had a viscosity fluctuation of ±2 mPa·s because insufficient ripening meant sodium ions did not fully penetrate the montmorillonite lattice, hydration equilibrium was not established, and performance stability was poor.

[0035] The filtration loss decreased with increasing bentonite A / bentonite B ratio and sodium carbonate dosage. The key mechanisms were: the increased proportion of bentonite B (high expansion ratio) formed a denser colloidal barrier after hydration, reducing water permeation into the formation; higher sodium carbonate dosage reduced the filter cake thickness from 1.2 mm to 0.9 mm and decreased the filter cake porosity by 15%, as the more fully sodium-treated particles were more tightly packed, enhancing the sealing ability; Comparative Example 1 had a filtration loss of 22 ml because no effective filter cake (3.0 mm thick, high porosity) was formed, allowing water to permeate freely; Comparative Example 2 had a filtration loss of 17 ml because the lack of bentonite C resulted in insufficient water retention capacity, significant drying shrinkage of the filter cake, and the appearance of microcracks; Comparative Example 3 had a filtration loss of 15 ml because the colloidal structure was not fully stable, the filter cake had low compressive strength, and was easily washed away by drilling fluid, leading to increased filtration loss.

[0036] Salt resistance significantly increased with increasing A / B ratio and sodium carbonate dosage. Reasons: High montmorillonite content in A, combined with high expansion ratio in B, forms a denser colloidal network, hindering Na⁺ / Cl⁻ penetration; 6% sodium carbonate increases the absolute value of the system's zeta potential from -30mV to -35mV (measured by a potentiometer), enhancing interparticle repulsion and improving resistance to salt ion aggregation; Comparative Example 1, lacking sodium carbonate, suffered system collapse due to salt ions directly disrupting the loose structure of the calcium-based bentonite; Comparative Example 2, lacking bentonite C, had insufficient water retention, making it prone to particle flocculation due to salt ions, resulting in a viscosity retention rate of only 70%.

[0037] High-temperature stability: In the examples, the increase in filtration loss after high temperature decreased with the increase of sodium carbonate dosage because: a higher degree of sodiumification makes the montmorillonite crystal layers more firmly bonded and less prone to depolymerization at high temperatures; sodium humate and triethanolamine work synergistically to maintain the hydration film on the particle surface at high temperatures; while in Example 2, which lacked bentonite C, the increase in filtration loss at high temperature reached +6 ml, because insufficient water absorption caused the filter cake to dehydrate and crack rapidly at high temperatures; in Comparative Example 3, insufficient curing accelerated the destruction of the unstable structure at high temperatures, resulting in an increase in filtration loss of +4 ml.

[0038] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-performance compound bentonite for drilling mud, characterized in that, It contains the following raw materials in parts by weight: 80-100 parts of mixed bentonite, 4-6 parts of sodium carbonate, 0.3-0.5 parts of sodium humate, 0.2-0.4 parts of triethanolamine and 0.2-0.4 parts of surfactant; The mixed bentonite is made by mixing bentonite A, bentonite B and bentonite C, and the ratio of bentonite A, bentonite B and bentonite C is 1:1:1 to 2:2:

1.

2. The high-performance compound bentonite for drilling mud according to claim 1, characterized in that: The bentonite A contains 56.3% montmorillonite, has an expansion ratio of 16 ml / 2g, and a water absorption rate of 221%; the bentonite B contains 48.9% montmorillonite, has an expansion ratio of 23 ml / 2g, and a water absorption rate of 189%; the bentonite C contains 52.8% montmorillonite, has an expansion ratio of 15 ml / 2g, and a water absorption rate of 208%.

3. The high-performance compound bentonite for drilling mud according to claim 1, characterized in that: The surfactant is selected from sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether.

4. A method for preparing high-performance compound bentonite for drilling mud, characterized in that, The preparation of a high-performance compound bentonite for drilling mud according to any one of claims 1-3 includes the following steps: I. Bentonite A, Bentonite B and Bentonite C are dried separately, then ground and pulverized, and finally sieved through a 150-mesh standard sieve. II. Weigh out the treated bentonite A, bentonite B and bentonite C according to the proportions. Add bentonite A, bentonite B and bentonite C into the mixer and mix to obtain mixed bentonite. Set the mixing speed to 15 r / min and the mixing time to 30 minutes. III. Weigh out a quantity of the mixed bentonite and place it in the mixing tank of a high-speed mixer, while simultaneously preparing a sodium carbonate solution; IV. Add deionized water to the mixing tank, and control the water temperature at 25±2℃. Turn on the mixer and stir at a low speed of 3000r / min for 5 minutes to initially disperse the mixed bentonite. Slowly pour in the prepared sodium carbonate solution to carry out the sodiumization reaction. Adjust the speed to 11000r / min and stir for 20 to 25 minutes. During this period, use an infrared thermometer to monitor the temperature of the liquid. If it exceeds 35℃, stop stirring for 2 minutes to cool down. V. Weigh out sodium humate, triethanolamine and surfactant separately. After stirring for 15 minutes, keep the speed at 11000 r / min and add sodium humate, triethanolamine and surfactant to the mixing tank in sequence. Continue stirring for 5 minutes to ensure that the mud bentonite additive and the mixed bentonite particles are fully adsorbed. VI. After mixing, turn off the mixer and transfer the liquid to a constant temperature maturation tank. Let it stand at a constant temperature of 25°C for 24 hours for maturation treatment, and finally produce high-performance compound bentonite. VII. After the samples pass the test, they should be sealed and stored.

5. The method for preparing high-performance compound bentonite for drilling mud according to claim 4, characterized in that, In step I, the drying process includes the following steps: A1. Take bentonite A, bentonite B and bentonite C, put them into the dryer respectively, set the drying temperature to 60-80℃, dry for 4-6 hours, and take them out when the moisture content is ≤5%. A2. The dried bentonite is then fed into a vibratory mill and an air jet mill in sequence. The vibratory mill rotates at 1200 r / min and is pulverized to a particle size ≤1 mm. The air jet mill operates at a pressure of 0.6-0.8 MPa and is pulverized to a particle size ≤106 μm. A3. After crushing, the material is screened through a 150-mesh vibrating screen. The residual particles on the screen are returned to the airflow pulverizer for re-crushing, and the material under the screen is temporarily stored in a sealed storage tank.

6. The method for preparing high-performance compound bentonite for drilling mud according to claim 4, characterized in that, In step II, during the preparation of the mixed bentonite, the material adhesion to the wall is checked every 10 minutes through the observation window. If the amount of material adhering to the wall is ≥5%, the machine is stopped and the tank wall is purged with 0.4MPa compressed air to ensure that the material is fully involved in the mixing.

7. The method for preparing high-performance compound bentonite for drilling mud according to claim 4, characterized in that, In step III, the preparation of the sodium carbonate solution includes the following steps: B1. Calculate the amount of sodium carbonate to be used based on 4% to 6% of the mass of the mixed bentonite and weigh it into the mixer. B2. Add deionized water to the stirrer and stir thoroughly to completely dissolve the sodium carbonate. B3. During the dissolution of sodium carbonate, measure the solution temperature. If it exceeds 25°C, place the beaker at room temperature for 5-10 minutes and cool it to 20-25°C. B4. After preparation, collect the sodium carbonate solution for later use.

8. The method for preparing high-performance compound bentonite for drilling mud according to claim 4, characterized in that, In step VI, during the maturation process, the bottom agitator is turned on for 5 minutes every 6 hours, and the agitation speed is 50 r / min.

Citation Information

Cited By

  • Slurry preparation clay for 240 DEG C saturated salt water-based drilling fluid as well as preparation method and application of slurry preparation clay

    CN121914690A